Induced polarization signature of coal seam fires. Issue 3 (1st December 2016) - Shao, Zhenlu; Revil, André; Mao, Deqiang; Wang, Deming
Abstract: Coal seam fires are a worldwide disaster of both ecological and economic importance. Their remote detection from the ground surface or using airborne techniques is required for developing efficient strategies to extinguish them. We investigate here the use of time-domain-induced polarization to localize coal seam fires. For laboratory experiments, we first introduce a modified time-domain-induced polarization methodology to quickly acquire and invert the secondary voltage distribution mapped after the shutdown of the primary current. A set of sandbox experiments is conducted in which coal is embedded into humidified sand. Raw coal alone generates significant induced polarization anomalies, above those shown by the sand. Even higher induced polarization anomalies are detected in presence of a coal seam fire. We postulate that the higher chargeability is due to the pyrolysis, which may enhance electronic polarization or the polarization associated with the cation exchange capacity (CEC) of the material. The position of the coal seam fire is well recovered inside the tank by inverting the secondary voltages in term of a source current density distribution. We also collected field data over a recognized coal seam fire in Colorado, USA. A chargeability anomaly (∼800 mV V −1 ) and a resistivity anomaly (∼1 Ohm m) are observed at the position of the coal seam fire. We propose a normalized burning front index (a scaled normalized chargeability) to image and localize, without ambiguity, the position of the coal seam fire in the subsurface. The 3-D reconstructed target is located below a negative self-potential anomaly (similarly to what is observed in laboratory experiments) and a temperature anomaly recorded at a depth of 30 cm.